2018
DOI: 10.1111/nep.13048
|View full text |Cite
|
Sign up to set email alerts
|

Association between resting heart rate just before starting the first dialysis session and mortality: A multicentre prospective cohort study

Abstract: The resting heart rate just before starting the first dialysis session was associated with all-cause mortality after dialysis initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The initial time-point for the survival analysis was the date of baseline echocardiography (prescheduled routine echocardiography). Cox proportional hazards analyses were performed using ASA, AVCS, MVCS, and other echocardiographic and clinical variables, including parameters that are considered risk factors for the primary endpoint [2,23,[27][28][29][30][31][32][33]. Regarding the incidence of the primary endpoint, up to five variables that achieved P-values < 0.05 in the univariable analyses were available in the multivariable Cox proportional hazards analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The initial time-point for the survival analysis was the date of baseline echocardiography (prescheduled routine echocardiography). Cox proportional hazards analyses were performed using ASA, AVCS, MVCS, and other echocardiographic and clinical variables, including parameters that are considered risk factors for the primary endpoint [2,23,[27][28][29][30][31][32][33]. Regarding the incidence of the primary endpoint, up to five variables that achieved P-values < 0.05 in the univariable analyses were available in the multivariable Cox proportional hazards analyses.…”
Section: Discussionmentioning
confidence: 99%
“…HR is associated with disease prognosis. Inaguma et al ( 29 ) reported that, in a multicenter prospective cohort study of 1,102 dialysis patients, resting HR before the first dialysis was found to be associated with all-cause mortality after starting dialysis. Patients with HR ≥ 101 bpm had significantly higher all-cause mortality than those with HR between 80 and 100 bpm, suggesting that HR may have a predictive value for disease regression.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 1102 new HD patients found that those with a resting heart rate >100 beats/min before their initial dialysis (N = 69) had an adjusted all‐cause mortality rate 2.3‐fold higher than those with a heart rate of 80‐100 beats/min. Patients with heart failure, atrial fibrillation, beta blocker use, and other confounders were excluded from the study …”
mentioning
confidence: 99%
“…Patients with heart failure, atrial fibrillation, beta blocker use, and other confounders were excluded from the study. 6 Continuous cardiac rhythm monitoring using implant loop recorders was performed in 66 HD patients for up to 1 year. Clinically significant arrhythmias were detected 1678 times in 44 patients (most often bradycardia, <40 beats/min; N = 1461).…”
mentioning
confidence: 99%